Pengaruh Financial Distress, Free Cash Flow, dan Earning Power terhadap Manajemen Laba - Ulvi Zuhrotul Faukha; Suwarno Suwarno (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to analyze the influence of financial distress, free cash flow, and earning power on earnings management. The sample for this research is mining companies listed on the Indonesia Stock Exchange (BEI), totaling 17 companies during the 2018-2022 period. Data was taken from the company's financial reports using a purposive sampling method. The type of hypothesis testing used is the T test (partial) with multiple linear regression analysis. The research results show that financial distress has a positive effect on earnings management, free cash flow has a negative effect on earnings management, while earning power has no effect on earnings management.